Desenvolvimento de protocolo clínico para atendimento à infertilidade na Atenção Básica à Saúde - Dias, Andrezza Alves (2015)
Infertility is the inability of a couple to achieve pregnancy after a year of unprotected sexual intercourse (at least twice a week). In Primary Health Care (PHC), we verify the demands from people with infertility complaints; however, health professionals working at this level of attention usually have low knowledge to manage this clientele. Knowing that protocols are instruments that standardize the care and favor the quality of actions, this study aimed to develop a clinical protocol for nursing care to infertility in PHC and evaluate its quality. Development or technological research conducted from January 2013 to March 2015 in 10 stages: problem definition, justification, defining the protocol content, literature review, algorithm construction, textual elaboration, collecting models, selecting and creating illustrations, layout, consulting with judges, and Portuguese review. Content definition occurred through brainstorming technique comprising clinical nurses, professors and users of family planning services. In order to substantiate the content, integrative reviews and the classification of scientific evidences according to the Oxford Centre for Evidence-based Medicine took place. A designer created the illustrations and layout of the material, in accordance with Brazilian Regulatory Norms, NRB 14724 and 6029. Seven judges assessed the protocol quality through the Appraisal of Guidelines Research and Evaluation (AGREE II), which is a 23-item tool comprising 6 domains, also including an overall assessment. The scores given by judges were calculated and analyzed in the light of the AGREE II, and presented in tables and figures generated in Microsoft Excel® software, version 2013. We calculated the Pearson’s Coefficient of Variation (PCV) by domains and the mean for the AGREE II items. The Research Ethics Committee of the Universidade Federal do Ceará, under protocol No. 544,069/2014, approved the research project. The judges had an average training time of 15.14 years, all had experience in family planning (birth control) and five reported experience in family planning focused on conception as well. With regard to the assessment of protocol quality, domain 6 (editorial independence) received the highest score from appraisers (98.8%). Domains 1 (scope and purpose) and 4 (clarity of presentation) were also greater than or equal to 90.0%. Domain 3 (rigor of development) reached the quality percentage of 89.3% and domain 2 (stakeholder involvement) had 83.3%. The lowest percentage belonged to domain 5 (applicability), 79.2%, mainly due to item 21, which evaluates the existence of criteria for monitoring and/or audit purposes. PCV analysis revealed a higher dispersion degree of the evaluation percentage in domain 5 (16.5%) given the greater variation of scores attributed. In the overall assessment, six judges gave score 7 “highest quality possible” and only one gave score 6, totaling 97.6%. No judge opposed to recommend the use of the protocol. We suggest that further research can perform the monitoring and/or audit of the implementation of this clinical protocol.